Advanced cathodes for potassium-ion batteries with layered transition metal oxides: a review. Issue 13 (16th March 2021) - Li, Wen; Bi, Zimo; Zhang, Wenxin; Wang, Jian; Rajagopalan, Ranjusha; Wang, Qiujun; Zhang, Di; Li, Zhaojin; Wang, Haiyan; Wang, Bo
Abstract : The research progress of layered transition metal oxide (LTMO) cathode materials in potassium-ion batteries (PIBs) is summarized. The key technical issues and scientific challenges faced by LTMO cathode materials in PIBs are analyzed. Abstract : The development of lithium-ion batteries (LIBs) is facing a huge challenge due to high cost and insufficient lithium resources. With the large-scale application of electric vehicles and portable electronics, the demand for LIBs is growing rapidly. In this connection, it is urgent to find a new secondary battery technology to make up for the shortcomings of LIBs. Potassium-ion batteries (PIBs) with low cost and high efficiency have drawn much attention. Particularly, layered transition metal oxides (LTMOs) with large interlayer distance and diffusion paths have been intensively investigated as cathode materials for PIBs. However, LTMO cathode materials often exhibit unsatisfactory electrochemical performance caused by the large potassium ion radius. To this end, this review mainly summarizes the progress of the research on LTMO cathode materials in PIBs. Meanwhile, the potassium storage mechanism and structural transformation are also analyzed for different metal-based LTMO cathode materials (single metal materials, dual-metal-based materials and multi-metal-based materials). What's more, the key technical issues and scientific challenges faced by LTMO cathode materials in PIBs are analyzed. This review provides constructive insights into the development of PIBs based on LTMOs.